Chemical composition of ferromanganese nodules from a core taken in the vicinity of the Hawaiian Islands - L Ye Shterenberg; T G Yeliseyeva; O S Lomova; Lidiya S Fomina (PANGAEA, 2023)
Ferromanganese nodules were retrieved at different levels inside a core taken in the vicinity of the Hawaiian Islands. Total iron contents were determined by the bichromate method with reduction by a bismuth reducing agent. Mn total content was determined by the volumetric arsenite-nitrate method, MnO2 content was determined from the active oxygen, and the MnO content was the difference between Mn total and MnO2.